Hydrogels for Two‐Photon Polymerization: A Toolbox for Mimicking the Extracellular Matrix. (27th May 2013) - Torgersen, Jan; Qin, Xiao‐Hua; Li, Zhiquan; Ovsianikov, Aleksandr; Liska, Robert; Stampfl, Jürgen
Abstract The natural extracellular matrix (ECM) represents a complex and dynamic environment. It provides numerous spatio‐temporal signals mediating many cellular functions including morphogenesis, adhesion, proliferation and differentiation. The cell–ECM interaction is bidirectional. Cells dynamically receive and process information from the ECM and remodel it at the same time. Theses complex interactions are still not fully understood. For better understanding, it is indispensable to deconstruct the ECM up to the point of investigating isolated characteristics and cell responses to physical, chemical and topographical cues. Two‐photon polymerization (2PP) allows the exact reconstruction of cell specific sites in 3D at micro‐ and nanometer precision. Processing biocompatible synthetic and naturally‐derived hydrogels, the microenvironment of cells can be designed to specifically investigate their behavior in respect to key chemical, mechanical and topographical attributes. Moreover, 3D manipulation can be performed in the presence of cells, guiding biological tissue formation in all stages of its development. Here, advances in 2PP microfabrication of synthetic and naturally based hydrogels are reviewed. Key components of photopolymerizable hydrogel precursors, their structure–property relationships and their polymerization mechanisms are presented. Furthermore, it is shown how biocompatible 2PP fabricated constructs can act as biologically relevant matrices to study cell functions and tissue development.